Stateful Logic Operation of Gated Silicon Diodes for In‐Memory Computing - Jaemin Son; Juhee Jeon; Kyoungah Cho; Sangsig Kim (Advanced Electronic Materials, 2024)
Abstract In‐memory computing significantly reduces workload and energy cost of data access in the traditional von Neumann computing architecture. Using various memristors, stateful logic is developed to realize in‐memory computing. However, memristors have encountered critical issues in terms of device variation and reliability, and therefore, fundamental device solutions are required to realize practical stateful logic. In this study, NAND, NOR, and half‐adder stateful logic operations of gated silicon diodes with a p+–n–p–n+ structure are demonstrated to achieve in‐memory computing. Gated diodes have bistable, steep switching, and quasi‐nonvolatile memory characteristics, enabling reliable stateful logic operation. The uniformity of their device characteristics overcomes the inherent stochastic characteristics of memristors that are widely researched for stateful logic. The sequential multiread logic operation simplifies the complex state logic scheme. In particular, a nondestructive half‐adder operation can be executed in five sequential steps using six parallel diodes. Thus, the stateful logic of gated diodes can be a potential building block for in‐memory computing.